2019
DOI: 10.7896/j.1910
|View full text |Cite
|
Sign up to set email alerts
|

The local food system in the ‘genius loci’ – the role of food, local products and short food chains in rural tourism

Abstract: This article investigates the roles that locally produced, processed and marketed food (Local Food System) play in rural tourism and local socio-economic development. It is the first account of a 3 years' research project (LO-KÁLI) exploring a successful Hungarian rural tourism destination, investigating both the demand side (what attracts tourists to pay for premium products/services); and the supply side (what attitudes, norms, values keep producers in their business). We contrast the externally perceived im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…One aspect is that this particularly happens in association with the development of tourism (Nemes et al 2019). Our results showed that tourism is attracted by those landscapes whose products help preserve the biocultural diversity and that in those cases, landscape product farmers are better off than the other local farmers, revealing interesting synergies between the benefits of the landscape product and the tourism sector.…”
Section: Characteristics Of the Landscape Productsmentioning
confidence: 71%
See 1 more Smart Citation
“…One aspect is that this particularly happens in association with the development of tourism (Nemes et al 2019). Our results showed that tourism is attracted by those landscapes whose products help preserve the biocultural diversity and that in those cases, landscape product farmers are better off than the other local farmers, revealing interesting synergies between the benefits of the landscape product and the tourism sector.…”
Section: Characteristics Of the Landscape Productsmentioning
confidence: 71%
“…Therefore, the question remains of whether these benefits can compare to those in rural nonfarm activities and in cities (le Polain de Waroux and Lambin 2013). This also poses threats to landscape sustainability, such as an uneven distribution of tourism-generated wealth within the local community, the appropriation of distinctive traditions by some actor groups (Bowen and De Master 2011), an overdependence on tourism (Nemes et al 2019), and a 'Disneyfication' of landscapes (Bowen and De Master 2011). To navigate these challenges, the social-organisational context needs to be taken into account, 'ensuring the representation of all actors, privileging local actors in the construction and governance of protective arrangements, considering local needs and priorities' (Bowen and De Master 2011, p. 81).…”
Section: Characteristics Of the Landscape Productsmentioning
confidence: 99%
“…Agritourism activities are only captured in a limited manner. 2 While the Census of Agriculture reports direct-to-consumer sales and agritourism as separate activities, considering both together more accurately reflects consumers' views and their experiences, as noted in Nemes et al (2019), Chase et al (2018) and Sgroi et al (2014). In addition, popular agritourism-type activities, such as the experience of cutting Christmas trees, are not considered in either category.…”
Section: Data and Caveatsmentioning
confidence: 99%
“…A továbbiakban tárgyalt másik vizsgálat a Lo-Káli, Mítosz és realitás, helyi élelmiszerrendszer a "Magyar Provence"-ban -diskurzusok, termelők, vásárlók és társadalomgazdasági hatások című, 2018 végén kezdődött kutatási program (Nemes et al 2019), ami a Káli-medence helyi élelmiszerrendszerét kutatja az NKFIH támogatásával (NKFI-6 K 129097). Ennek során a kétezer-tízes-húszas évek fordulóján helyi termelőkkel (Balogh 2022), turisztikai vállalkozások tagjaival és bevállalkozókkal (Nemes et al 2022), a medencébe különböző időszakokban beköltözőkkel (Lajos-Nemes 2020), a helyi társadalom tagjaival és turistákkal készítettünk félig strukturált interjúkat és vettünk fel zárt és nyílt kérdéseket tartalmazó kérdőíveket.…”
Section: Iii1 a Két Kutatási Időszakban Alkalmazott Módszerek Témák é...unclassified